Estimating the diameter of reinforcing bars using an ultra-wideband MIMO GPR array - Cheng, Weixia (2023)
Ground-penetrating radar (GPR) is an effective non-destructive detection technology for locating and characterizing reinforcing bars in concrete structures. However, the accurate quantification of reinforcing bar diameters, especially in small-diameter cases, remains a challenging issue. In this paper, a sizing method based on multiple-input-multiple-output (MIMO) GPR arrays is presented to estimate the reinforcing bar diameter in concrete. The method employs a linear array of ultra-wideband (UWB) antennas to acquire the full-matrix MIMO data of the reinforcing bar embedded in concrete. The diffraction stacking algorithm is applied to the obtained MIMO data to reconstruct the reinforcing bar. The 3 decibels (dB) drop technique is used to measure the chord length that passes through the peak intensity point of the reconstruction image of the reinforcing bar. Following that, the diameter of the reinforcing bar can be determined based on its cover depth and the chord length. Extensive numerical studies and experiments have been conducted to examine the performance of the proposed method in different scenarios. The method shows excellent sizing accuracy for reinforcing bars with different diameters and cover depths.